Perlindungan hukum Perlindungan Hukum Terhadap Pasien Sebagai Pengguna Fitur Layanan Kesehatan di Aplikasi Fisdok - Kuswardani, Kuswardani; Abidin, Zainal (Fakultas Syariah INSURI Ponorogo, 2023)
FisDok is a telemedicine healthcare application created by UWHS Physiotherapy students. In health services, this can create an engagement relationship between the provider and recipient of health services, while the provider of the FisDok application platform only functions as a provider of teleconsultation facilities. Patients who get telemedicine services must get legal protection, because there are opportunities for malpractice. This study aims to examine with a sociological juridical approach, descriptive analytic research specifications, the data used are in the form of primary and secondary data to examine whether the FisDok application is safe for consumers of telemedicine services. The method of data collection is literature study and field study, the population is all patients, doctors and physiotherapists who are involved and registered in the FisDok application, samples are taken by non-random sampling with purposive sampling type, namely all 10 patients, 1 doctor, and 4 physiotherapists people and analyzed qualitatively. The results of the study show that the implementation of legal protection for patients as users of the FisDok application has been carried out well, it is proven that health workers already have an STR an accordance, particularly law no. 36 of 2014 and PerMenKes No. 20 of 2019.